Development of Learning Media Using Google Site with Flipped Classroom Model to Improve Social Studies Learning Outcomes in Junior High School Students Negeri 2 Siempat Nempu Hulu - Laristina Sinaga; Samsidar Tanjung; Abdul Hamid K (The Eastasouth Journal of Learning and Educations, 2026)
This research aims to develop and evaluate Google Site-based learning media that is integrated with the flipped classroom model in social studies learning at SMP Negeri 2 Siempat Nempu Hulu. The research uses a Research and Development (R&D) approach with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. A mixed methods approach is used by combining qualitative and quantitative data. The research subjects were grade VIII students who were divided into experimental and control classes using cluster random sampling techniques. Data collection was carried out through expert validation, student response questionnaires, observations, interviews, and pretest and posttest tests. The developed media integrates pre-class, in-class, and post-class activities through videos, images, interactive LKPDs, reflections, and digital evaluations. The results of validation of material, media, and learning design experts show a percentage of eligibility above 90% with the very feasible category. The students' responses also showed excellent categories. The effectiveness results showed that the experimental class obtained an N-Gain value of 0.72 (high), while the control class obtained a value of 0.41 (moderate). These findings show that flipped classroom-based Google Site media is effective in increasing student social studies engagement, independence, and learning outcomes.